Effect of Temperature and Alcohol on the Determination of Critical Micelle Concentration of Non- Ionic Surfactants in Magnetic Water - Aamer A. Al-Hatem (مجلة بغداد للعلوم)
The determination of critical micelle concentration of selected non-ionic surfactants (Tween 20,40 and 80) have been investigated using magnetic water(MW)as an aqueous medium.Conductometry technique is used to determine critical micelle concentration.The effect of alcohol addition and temperature variation at the range(293.15 -303.15K) are also pursued. It is concluded that the process of micellization is spontaneous and endothermic because of the observed free energy of micellization (ΔGom) , enthalpy change of micellization  (ΔHom), and entropy change of micellization (ΔSom) for the system was also studied.The properties of the non-ionic surfactants were studied, both in absence and presence of alcohol. The results obtained were explained in light of hydrophobic-hydrophilic interactions and chain length of alcohol.The temperature change has slight effect on the micellization process. .